PREDIKSI KUNJUNGAN PASIEN RAWAT JALAN DI RSAU dr. SISWANTO LANUD ADI SOEMARMO KARANGANYAR TAHUN 2022-2026 - Eni Nur Rahmawati; Mia Ayu Laras (Universitas Duta Bangsa Surakarta, 2023)
Predictions of outpatient visits can be used as a reference in management decision making such as planning service management, facilities and human resources in a hospital. The number of outpatients in 2017-2021 has increased and decreased. The purpose of this study was to determine the prediction of outpatient visits in 2022-2026. The type and design of this research is descriptive with a retrospective approach. The population and sample of this study are the 2017-2021 outpatient daily census recapitulation. Data collection techniques using observation and interview methods. The research instrument used interview guidelines, observation guidelines, work tables, 2017-2021 calendars and calculators. Outpatient indicator predictions for 2022-2026, the average patient visits per day increased by (0.70), the average new patient visits were stable, the average old patient visits increased by (0.70), the ratio of new visits to total visits was stable, the ratio of old visits to total visits was stable, the percentage of specialist services in 4 polyclinics increased (2.007 orthopedics, 0.080 general surgery, 1.220 eye and 0.306 lung), while the prediction of 8 polyclinics decreased (-2.972 internis, -2.004 pediatrics, -1.369 obsgyn, -0.374 ENT, -0.834 neuro, -0.039 psychiatry, -0.067 genital skin and -0.003 cardiology), the ratio of visits to the number of nurses increased by (0.20), the ratio of patients to the population was stable. Prediction of outpatient visits at RSAU dr. Adi Soemarmo Karanganyar Lanud students in 2022-2026 tend to increase, decrease and stable. Hospitals should carry out promotions, outreach to the community regarding the types of services and facilities they have, in order to increase public trust.